Titanium dioxide based hybrid photocatalyst for seawater desalination pre-treatment - Weerana, Eh Kan (2016)
The application of hybrid titanium dioxide (TiO2) photocatalyst in treating water resources has huge economic potential and an attractive alternative technology for seawater pre-desalination. The objective of this investigation is to study the effectiveness of photocatalytic reactor system via hybrid photocatalyst that content oil palm fiber ash (OPFA), TiO2 and metal promoter in the seawater desalination pre-treatment. The study was carried out in a one liter borosilicate photoreactor for 1 hr to 4 hrs. The catalyst to seawater sample weight ratio was varied from 1:300 to 1:500. The experiment was carried out by using mercury light (UV light) and halogen light (visible light). The chemical oxygen demand (COD), pH, dissolved oxygen (DO), turbidity, total dissolved solid (TDS) and conductivity of the seawater were analyzed prior and after the treatment. The fresh and spent catalysts were characterized via X-ray diffraction (XRD), scanning electron microscopy (SEM), N2 adsorption, ultraviolet visible near-UV/near-infrared (UV/Vis/Nir), elemental analysis (carbon, hydrogen, nitrogen and sulphur (CHNS)) and X-ray fluorescence (XRF). The gas product was analyzed by using gas chromatography with thermal conductivity detector (GC-TCD). The TiO2 catalyst can reduce salt concentration for more than 7 % and decrease up to 8 % of COD. The OPFA was able to adsorb about 3 % of salt in either with the present or absent of lights. Furthermore, OPFA reduced seawater COD for more than 10 % the light presence and 4 % in without light present. The hybrid catalyst containing TiO2:Ash 50:50 was calcined at 500 °C, reduced more than 9 % of salt and 24 % of COD reduction in the seawater. It is found that the TiO2:Ash 50:50 catalyst has dual functions, ie. the catalyst was able to adsorb the salt and decompose the water contaminants resulting in lower conductivity and COD in the seawater. However, the hybrid TiO2:Ash 50:50 catalyst which calcined at 800 °C was only able to reduce 2 % of salt and 14 % of COD reduction in the seawater. Better TiO2:Ash 50:50 catalyst reactivity was achieved when UV light was used than visible light. Higher water temperature was observed when visible light was applied that leads to distillation dominating the process. The optimum parameters for photocatalytic reaction was obtained by using hybrid TiO2:Ash 50:50 catalyst when catalyst to water weight ratio was at 1:400 and operating for 2 hrs. Iron (Fe) and nickel (Ni) can be loaded into the catalyst. Fe loading in the catalyst was found to perform better than Ni. The best condition was obtained when visible light and TiO2:Ash:Fe 47.5:47.5:5 were used. The TiO2:Ash:Fe 47.5:47.5:5 reduced 16 % and 22 % of salt concentration and COD respectively. While, the TiO2:Ash:Ni 47.5:47.5:5 was only able to reduce up to 13 % of salt in the seawater and decrease 22 % of seawater COD at the same condition. In conclusion, better water quality can be achieved via photocatalytic reaction by using hybrid photocatalyst. Thus, the photocatalysis process is able to provide an effective alternative pre-treatment for seawater desalination.